2018
DOI: 10.1177/1474474018787278
|View full text |Cite|
|
Sign up to set email alerts
|

The hidden geographies of religious creativity: place-making and material culture in West London faith communities

Abstract: Religious activity, particularly as associated with what might be called everyday organized religion, has been unconsidered in recent discussions of the geographies and policies relating to creativity, and has been almost absent in the discipline of Geography's recent 'creative turn'. We argue both that religion has been given little or no attention in academic discussions of vernacular creativity, while arts policy as it developed in the UK in the post-war period has had a strongly secular focus. This continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Churches, church halls, mosques, synagogues, gurdwaras, temples, stupas. (Dwyer, Gilbert, & Shah, 2013), Gilbert, Dwyer, Ahmed, Graces, & Hyacinth, 2019), (Ehrkamp & Nagel, 2014), (Levitt, 2008).…”
Section: Religionmentioning
confidence: 99%
“…Churches, church halls, mosques, synagogues, gurdwaras, temples, stupas. (Dwyer, Gilbert, & Shah, 2013), Gilbert, Dwyer, Ahmed, Graces, & Hyacinth, 2019), (Ehrkamp & Nagel, 2014), (Levitt, 2008).…”
Section: Religionmentioning
confidence: 99%
“…The recruitment for the Fabric of Faith project began from our existing research within the different faith communities, which had identified vernacular textiles as a particularly interesting example of religious creativity. Our initial research suggested a rich vein of decorative textiles produced by members of suburban faith communities for use at home, in communal and congregational religious settings, and for sale or distribution as part of faith-based, often transnational, philanthropy (see Gilbert et al 2019). Having identified groups in each of these different faith communities with interests in sewing, our intention was to bring some of them together to participate in a creative textiles project.…”
Section: Participation and Making As Convivial Practicementioning
confidence: 99%
“…As a research tool, the Fabric of Faith workshops proved a very successful means to gather an understanding of how creativity was integral to different communal religious identities and devotional practices (Gilbert et al 2019), and to explore intersections of faith, gender and migration. This research was a two-fold process.…”
Section: Participation and Making As Convivial Practicementioning
confidence: 99%
See 2 more Smart Citations